Homozygous mutations in REC114 cause female infertility characterised by multiple pronuclei formation and early embryonic arrest. Issue 3 (8th November 2019) - Wang, Wenjing; Dong, Jie; Chen, Biaobang; Du, Jing; Kuang, Yanping; Sun, Xiaoxi; Fu, Jing; Li, Bin; Mu, Jian; Zhang, Zhihua; Zhou, Zhou; Lin, Zhao; et al.
Abstract : Background: Abnormal pronuclear formation during fertilisation and subsequent early embryonic arrest results in female infertility. In recent years, with the prevalence of assisted reproductive technology, a few genes have been identified that are involved in female infertility caused by abnormalities in oocyte development, fertilisation and embryonic development. However, the genetic factors responsible for multiple pronuclei formation during fertilisation and early embryonic arrest remain largely unknown. Objective: We aim to identify genetic factors responsible for multiple pronuclei formation during fertilisation or early embryonic arrest. Methods: Whole-exome sequencing was performed in a cohort of 580 patients with abnormal fertilisation and early embryonic arrest. Effects of mutations were investigated in HEK293T cells by western blotting and immunoprecipitation, as well as minigene assay. Results: We identified a novel homozygous missense mutation (c.397T>G, p.C133G) and a novel homozygous donor splice-site mutation (c.546+5G>A) in the meiotic gene REC114 . REC114 is involved in the formation of double strand breaks (DSBs), which initiate homologous chromosome recombination. We demonstrated that the splice-site mutation affected the normal alternative splicing of REC114, while the missense mutation reduced the protein level of REC114 in vitro and resulted in the loss of its function to protect its partner protein MEI4 from degradation. Conclusions: Our study has identified mutations in REC114 responsible for human multiple pronuclei formation and early embryonic arrest, and these findings expand our knowledge of genetic factors that are responsible for normal human female meiosis and fertility.